2013
DOI: 10.1126/science.1227612
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of Scattering Rates in Metals Showing T -Linear Resistivity

Abstract: Many exotic compounds, such as cuprate superconductors and heavy fermion materials, exhibit a linear in temperature (T) resistivity, the origin of which is not well understood. We found that the resistivity of the quantum critical metal Sr(3)Ru(2)O(7) is also T-linear at the critical magnetic field of 7.9 T. Using the precise existing data for the Fermi surface topography and quasiparticle velocities of Sr(3)Ru(2)O(7), we show that in the region of the T-linear resistivity, the scattering rate per kelvin is we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
614
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(669 citation statements)
references
References 64 publications
50
614
3
2
Order By: Relevance
“…Recent experimental observations showing that a wide range of strange metals in the linear-in-temperature resistivity regime present an equilibration rate of this kind [1] strongly supports the idea that a unified framework might capture the properties of these strongly interacting materials.…”
Section: Jhep07(2015)102mentioning
confidence: 79%
See 1 more Smart Citation
“…Recent experimental observations showing that a wide range of strange metals in the linear-in-temperature resistivity regime present an equilibration rate of this kind [1] strongly supports the idea that a unified framework might capture the properties of these strongly interacting materials.…”
Section: Jhep07(2015)102mentioning
confidence: 79%
“…One of the best known examples is the linear-in-temperature resistivity regime shared by many apparently very different materials like cuprates, heavy fermions, pnictides, ruthenates and fullurenes [1]. In recent times, a great effort has been put into characterizing the universal behavior of these materials by determining bounds on appropriate physical quantities.…”
Section: Introductionmentioning
confidence: 99%
“…This state results in a unique type of heat transport carried by an incoherent composite fluid, which we dub the electron-phonon soup, characterized by an effective velocity vs < vB < vF . We suggest that such behavior is ubiquitous in strongly interacting complex systems at high temperatures and thus, propose that it may explain much of the anomalous transport in "bad metallic" systems [e.g., cataloged by Bruin et al (17) and discussed in terms of spectral weight transfer in refs. 3, 4, and 59].…”
Section: Significancementioning
confidence: 99%
“…Recently, this time scale has been observed in the scattering rates of materials showing a linear T resistivity [13] and in the thermal diffusivity [14].…”
Section: Jhep06(2017)030mentioning
confidence: 99%
“…It has been shown that the Lyapunov exponent is bounded by the temperature 13) and saturates to the bound 2π/τ P for thermal systems that have a dual holographic black hole description of which near horizon geometry is described by Einstein gravity. Notice that the Planckian time scale appears as a time scale of the growth of chaos in time.…”
Section: Jhep06(2017)030mentioning
confidence: 99%